Findings of specific antibodies against Leptospira interrogans in cattle blood sera - Grgić Živoslav (Veterinarski Glasnik, 2005)
Serological investigations were performed on 24,208 samples of cattle blood serum, representing 31.18% of the reproductive cattle fund in the territory of nine municipalities in the Southern Bačka region over a period of five years. The samples were examined using the method of microscopic agglutination, with live antigens of nine Leptospira serotypes: L. pomona, L. icterohaemorrhagiae, L. grippotyphosa, L. sejroe, L. tarassovi, L. australis, L. bataviae, L. canicola, and L. hardjo. Specific antibodies against leptospira were established in 286 or 1.18% samples of cattle serum. The level of seroprevalence of leptospira infection at an annual level ranged from 2.56% to 0.05%. The biggest number of seropositive cattle were registered in the municipality of Novi Sad-151 cattle, or 3.54%. In the course of the observation period, the presence of four serotypes of ieptospira were diagnozed in catlt: L. pomona, L. icterohaemorrhagiae, L. grippotyphosa, L. hardjo. The most represented serotype was L. hardjo, 41.02%, while the serotypes L. grippotyphosa (34.61%), L. icterohaemorrhagiae (14.74%) and L. pomona (9.61%) were diagnosed in smaller percentages. An increasing tendency was observed in the number of cattle infected with leptospira at an annual level of 0.195%. On the basis of the presented analysis, it can be predicted with a probability of 95%, that leptospirosis in cattle will appear within the range of 0.09% to 3.50% in the epizootiological region of Southern Bačka in the coming period.